The floating world in Japanese fiction - Hibbett, Howard (Oxford University Press, 1960)
This is a detailed study of ukiyo-zoshi, tales of the Floating World, and a fascinating look at the manners and customs, arts and affectations, of city life in Tokugawa-era Japan. Here are the rakish shopkeepers, teahouse women, celebrated actors, and ordinary townspeople, all obsessed with the pursuit of pleasure that characterised the Genroku period, a time when the aims and ideals of the urban merchant class took precedence over those of the samurai.